PRIVATISASI COLLECTIVE GOODS SUMBER DAYA EKSTRAKTIF BUDIDAYA LOBSTER UNTUK KESEJAHTERAAN SOSIAL MASYARAKAT KEPULAUAN MULUT SERIBU - Jacob, Ananias Riyoan Philip; Sabaat, Yeftha Yerianto; Triadmadja, Stefanus (Jurnal Dakwah Tabligh, 2024)
This study is aimed at discussing the governance of extractive natural resources of lobster farming in the thousand mouth islands - rote ndao district based on a basic argumentation: one, Privatization of Collective Goods and its implications for local communities. Second, the power relations between the government as a regulator and corporations that commercialize extractive resources of lobster farming in the Thousand Mouth Islands - Rote Ndao Regency. To analyze some of the above issues, the author uses the political ecology paradigm as a starting point. Political ecology sees resource and environmental management not only as technical issues in the field but also as a dialectic of the socio-political environment and the community where the resources are located.